Effectiveness of Bilateral Internal Jugular Parathyroid Hormone Measurements in Optimizing Hyperparathyroidism Surgery Outcomes - Davi Knoll Ribeiro; Murilo Catafesta das Neves; Rodrigo Oliviera Santos; Monique Nakayama Ohe; Marise Lazaretti‐Castro; Marcello Rosano; Marcio Abrahao (OTO Open)
Abstract Objective This study aimed to assess the effectiveness of intraoperative parathyroid hormone (PTH) measurements from bilateral internal jugular veins (BIJVs) in determining parathyroid gland laterality during surgery for primary hyperparathyroidism (PHPT). Study Design Prospective cohort study. Setting Single tertiary care center, February 2021 to February 2023. Methods All patients underwent intraoperative BIJV PTH measurements during parathyroidectomy. Preoperative localization of abnormal parathyroid glands was performed using cervical ultrasound (USG) and sestamibi scans (MIBI). Receiver operating characteristic (ROC) analysis was performed to determine the best performance (sensitivity and specificity) for predicting parathyroid gland laterality. Results A total of 124 patients underwent surgery during the study. PTH measurements from BIJV successfully confirmed the laterality of parathyroid adenomas in 102 cases (82.3%, P = .001). Intraoperative BIJV PTH measurements proved to be the most effective method for determining parathyroid gland laterality, with an accuracy of 82.3%. ROC curve analysis identified an optimal cutoff point of 16.7% for the percentage difference between right and left BIJV PTH values. The area under the curve (AUC) was 0.882, indicating high diagnostic accuracy. This cutoff yielded a sensitivity of 76.5% and a specificity of 95.5%. Additionally, no patients experienced complications related to the internal jugular vein (IJV) procedure. Conclusion Intraoperative BIJV PTH measurement is a valuable adjunct in parathyroidectomy, improving localization and enhancing surgical outcomes in PHPT patients.